Pemeliharaan Udang Putih Penaeus Marguensis pada Substrat dan Volume Media Air yang Berbeda terhadap Tingkat Kelangsungan Hidup dan Pertumbuhan - Hama, Rimal; Ardiansyah, Ardiansyah; Nursyahran, Nursyahran (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
This research aims to determine the effect of different substrates + water volume on the growth and survival rate of white shrimp Penaeus marguensis. This research was carried out from March to April 2019. The research was carried out experimentally using a Completely Randomized Design (CRD) with 3 treatments and 3 replications. The treatments tried were mangrove soil substrate + 36 liters of brackish water media, sand substrate + 45 liters of brackish water media, and 54 liters of plastic substrate. The sampling technique used is probability sampling with random sampling (simple random sampling). The research variables consist of absolute growth and survival rate. The highest absolute growth was obtained in the sand substrate treatment + 45-liter water media volume of 3.91 grams and the lowest was in the plastic substrate layer treatment + 54-liter brackish water media volume of 2.94 grams, and the highest survival rate was obtained in the sand + substrate treatment. the volume of 45-liter water media was 74% and the lowest was in the treatment of plastic substrate layer + 54-liter brackish water media volume of 53%. Meanwhile, water quality is in the optimal range for raising Penaeus marguensis shrimp. The results of the analysis of variance showed that the effect of water media volume on the growth and survival rate of Penaeus marquess shrimp had a significant effect.